2013
DOI: 10.2147/ijn.s39658
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular distribution of nontargeted quantum dots after natural uptake and microinjection

Abstract: Background:The purpose of this study was to elucidate the mechanism of natural uptake of nonfunctionalized quantum dots in comparison with microinjected quantum dots by focusing on their time-dependent accumulation and intracellular localization in different cell lines. Methods:The accumulation dynamics of nontargeted CdSe/ZnS carboxyl-coated quantum dots (emission peak 625 nm) was analyzed in NIH3T3, MCF-7, and HepG2 cells by applying the methods of confocal and steady-state fluorescence spectroscopy. Intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 48 publications
5
58
0
Order By: Relevance
“…The curve corresponded to the standard S-shaped sigmoid QD accumulation curve (lag, growth, and saturation stages). 43 For the first hour, the QD PL signal was low; after an hour, the PL signal sharply increased until 6 h at which time the transitional phase was reached. Since the results showed that incubation for 6 h is sufficient to obtain the early saturation phase of accumulation, 6 h incubation time point was chosen as the optimal QD incubation time ( Figure 3B).…”
Section: Optimization and Quantification Of Qd Internalizationmentioning
confidence: 98%
See 1 more Smart Citation
“…The curve corresponded to the standard S-shaped sigmoid QD accumulation curve (lag, growth, and saturation stages). 43 For the first hour, the QD PL signal was low; after an hour, the PL signal sharply increased until 6 h at which time the transitional phase was reached. Since the results showed that incubation for 6 h is sufficient to obtain the early saturation phase of accumulation, 6 h incubation time point was chosen as the optimal QD incubation time ( Figure 3B).…”
Section: Optimization and Quantification Of Qd Internalizationmentioning
confidence: 98%
“…QDs were localized inside the vesicles, demonstrating that endocytosis was their entry pathway ( Figure 4, insert b) -our previous study on QD microinjection, mimicking passive diffusion of nanoparticles, demonstrated that after microinjection or membrane damage, the QDs were uniformly dispersed in the cytoplasm of the cells and did not form any vesicular structures, proving endocytosis is responsible for vesicle formation. 43 …”
Section: Intracellular Localizationmentioning
confidence: 99%
“…[243][244][245] Yum et al presented a nanoscale mechanochemical method to deliver QDs into living cells using a membrane penetrating nanoneedle. This nanoneedle consisted of a chemically synthesized boron nitride nanotube, which was coated with a thin layer of Au.…”
Section: Cell Deliverymentioning
confidence: 99%
“…Furthermore, uptake of Qtracker ® 800 has not been reported for any cell type. Endocytosis, which is thought to be the main pathway for nanoparticle internalization [39,40], depends on Brain endothelial cells are activated by QDs Research Article nanoparticle size [41]. Specifically, endocytosis-mediated uptake of nanoparticles was found to be more efficient for hydrodynamic diameter values around 50 nm [42].…”
Section: Nontargeted Pegylated Near-infrared Emitting Qtracker ® 800 mentioning
confidence: 99%